(untitled) (Texas Journal of Philology, Culture and History, 2024)
English majors should possess vocabulary proficiency and language skills to excel in their field. This study aimed to investigate the various factors and significant impact of vocabulary proficiency and language skills development on the English majors at Cebu Normal University-Main Campus. Using a quantitative approach with a descriptive-inferential design, the research investigates the significance of demographic profiles in language development. A Likert scale, designed by the researchers, gauges factors affecting vocabulary and language skills in 71 randomly selected respondents from three different degree programs. Based on the findings, most of the respondents scored very high, indicating that these factors are likely to improve their vocabulary and language skills. Moreover, most respondents are female, and their socioeconomic status tends to be in the poor and lower-income categories. Findings suggest that there is a significant relationship between the respondents’ degree program with a p-value of 0.039608 and socioeconomic status with a p-value of 0.0001 and their vocabulary proficiency and language skills development, with gender showing no significance.